Epipactis bucegensis—A Separate Autogamous Species within the E. helleborine Alliance - Nora E. Anghelescu; Mihaela Balogh; Lori Balogh; Nicoleta Kigyossy; Mihaela I. Georgescu; Sorina A. Petra; Florin Toma; Adrian G. Peticilă (Plants, 2023)
A new species of Epipactis from Bucegi Natural Park ROSCI0013, Southern Carpathians, Central Romania is described. Three medium-sized populations of Epipactis bucegensis (65–70 individuals in total) were discovered in the south-eastern, subalpine area of the park. To properly describe and distinguish the newly found taxon from other Romanian Epipactis, 37 morphological characters were measured directly from living plants and flowers. Moreover, a detailed taxonomic treatment and description with corresponding colour photos and line drawings illustrations of the holotype are also included. Epipactis bucegensis is an obligate autogamous species that partially resembles Epipactis muelleri, from which it differs in the basal distribution of leaves on the stem (vs. median distribution); near-erect leaf posture (vs. horizontally spread, arched downwards); lanceolate–acuminate, yellowish-green leaves (vs. oval–elongate, vivid-green leaves); bipartite labellum lacking the mesochile (vs. tripartite labellum); crimson-red, wide, ovoid–elongated, flattened hypochile (vs. dark-brown to black roundish hypochile); triangular, white epichile with a sharply tapering apex (vs. heart-shaped, greenish-yellow epichile with obtuse, roundish apex); and two wide-apart, purple, pyramidal calli (vs. two closely placed, attenuated, mildly wrinkled, greenish-yellow calli). Epipactis bucegensis is easily distinguished from all other European Epipactis taxa by the bipartite, wide labellum that lacks the mesochile. In addition, information regarding its distribution (maps), habitat, ecology, phenology and IUCN conservation assessments are provided.